THE ROLE OF GOVERNMENT AND COMMUNITY IN DEVELOPING SUAYA STONE GRAVEYARD TOURIST ATTRACTION IN SANGALLA SUB-DISTRICT, TANA TORAJA DISTRICT - Balik, Wesni (Geographica: Science and Education Journal, 2024)
This research is motivated by the role of the government and the community in developing Grave Tourism Objects in Sangalla District, Tana Toraja Regency. The purpose of this research is to find out how the role of the government and the community in developing the Batu Suaya Graveyard Tourism Object. This research uses a qualitative descriptive method. The data analysis techniques used in this research are data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that in developing the Suaya Stone Graveyard tourist attraction. The Tana Toraja Tourism Office, which acts as a facilitator, innovator and regulator, cooperates with the community, both the community of tourism object owners in this case the descendants of the Sangalla king who play an active role in the development of the Batu Suaya Graveyard Tourism Object and other local communities who act as marketers, implementers, participants and beneficiaries. The obstacles faced by the government in developing the Suaya Stone Graveyard Tourism Object are the lack of funds allocated for the construction of tourist attractions and for the community the obstacles experienced are the limitations of other community parties in making development efforts where the party that is more entitled to seek the development of Suaya stone graveyard tourism objects is the community of descendants of the king of Sangalla.